The COVID-19 Pandemic: Informing Policy Decision-Making for a Vulnerable Population - Spence, Nicholas; Chau, Vivian; Farvid, Maryam S.; White, Jerry P.; Rasalingam, Paranthaman; Loh, Lawrence (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
The COVID-19 pandemic has significantly impacted society. Vulnerable populations are at heightened risk for exposure, as well as adverse health and social consequences. Policymakers are operating under difficult circumstances, making crucial policy decisions to maximize impact and mitigate harm, with limited scientific evidence. This article examines the pronounced vulnerability of Indigenous Peoples in Canada to the pandemic. We highlight the importance of moving beyond individual-level risk factors associated with COVID-19 by identifying and classifying Indigenous communities most vulnerable to the pandemic. We propose the use of a social diagnostic tool, the Community Well-Being Index, rooted in the social determinants of health, to predict community vulnerability and potentially guide policy decision-making in the fight against COVID-19.